KERAGAMAN PENAMPILAN FENOTIP ENAM GENOTIPE PEPAYA HASIL PERSILANGAN - Sunyoto Sunyoto; Liza Octriana; Tri Budiyanti (Widyariset, 2014)
Getting new varieties according to consumer preferences   can be carried out through crossbreeding (hy bridization) between elected elders. The results of such crossbreeding must be characterized and sorted to obtain new superior varieties that show the expected appearance of phenotype. The research aimed to get information about phenotypical appearance diversity and heritability value of some characters of some papaya hybrids. The study was conducted from March 2011 to February 2012 at the Sumani Research Station, Tropical Fruit Research Institute. The research was arranged in a randomized block design with six treatments and three replications. Each unit consisted of eight plants. The results showed that the phenotypical appearances such as fruit weight, fruit girth, fruit cavity width, and a larger number of perfect flowers, was influenced by genetic factors and had high heritability values. Genotypes  P 13, P 14, P 21, and P 31 could be the superior variety candidates because of their early maturity, low height of first flower and first fruit, i.e. < 1 m (low bearing), medium-sized fruit, thick fruit flesh and sweet taste, and PTT > 13° Brix. Some of papaya hybrids are expected to be new superior varieties of papaya Indonesian.